Low anterior rectal resection; the impact of anastomotic fistula on incidence and severity of low anterior resection syndrome - Giorgiana Coțofană Graure; Cecil Mirea; Silviu Daniel Preda; Ștefan Pătrașcu; Tiberiu Stefanita Tenea-Cojan; Adina Turcu-Stiolica; Alexandru Munteanu; Vlad Padureanu; Dragos Margaritescu; Sandu Ramboiu; Dan Cartu; Valeriu Șurlin; et al. (Journal of Mind and Medical Sciences)
Objectives. Low anterior resection is a common surgical procedure for rectal cancer, but it is associated with a distressing complication known as Low Anterior Resection Syndrome (LARS). The incidence of LARS varies, with severe symptoms persisting in some patients even years after surgery. This study aimed to investigate the association between anastomotic leak and LARS severity in rectal cancer patients. Methods. A retrospective analysis was conducted on 100 rectal cancer patients who underwent LAR between 2017 and 2021. Patients were categorized based on LARS questionnaire responses into groups with anastomotic leakage and LARS, LARS alone, or no LARS. Various factors, including demographics, comorbidities, tumor characteristics, and surgical details, were analyzed for their association with LARS. Results. In our study, anastomotic leakage was observed in 23 patients, and 17 of them subsequently developed LARS. Male gender, age over 70, and neoadjuvant therapy were identified as risk factors for LARS. Additionally, LARS was more prevalent in patients with medium and low rectal cancers and those with a protective ostomy. Conclusion. Our findings suggest that male sex and neoadjuvant chemoradiotherapy are associated with the development of LARS in rectal cancer patients undergoing low anterior resection. The timing of stoma closure and the extent of neorectal reservoir may also impact LARS severity.